A rational fear? Pedagogy of fear in public discourse - Helena Ostrowicka; Aleksandra Rzyska (University of Lower Silesia, 2017)
This article aims to present the results of the critical analysis and interpretation of the debate on the issue of compulsory vaccination conducted in the weekly magazine Polityka in 2012. Based on the analysis of discursive strategies employed in the examined text, the constitutive role of the strategy of authorization has been found, which, because of excessive use of rhetorical devices and the power of "rhetoric of exclusion," paradoxically resulted in "the problem" of authority. The results have been discussed from a pedagogic perspective, which is particularly interested in educational consequences of discursive practices and pedagogy. In view of its particular organizational and ideological dimensions, the analyzed discourse was interpreted through the prism of persuasion and pathos relations in the pedagogy of fear-fear of the discursively constructed ENEMY.